Justice, Democracy and Reasonable Agreement - Farrelly, C. author. aut Link
XVI, 253 p.
Keywords: Farrelly argues against the principled paradigm of ideal theory and champions instead a virtue-oriented theory of justice entitled 'civic liberalism'. He critically assesses the main contemporary theories of justice and tackles a number of applied topics, ranging from constitutional design and free speech to welfare reform and economic incentives.